Editorial – CAGA 2024 - Fyhn, Bue Holmsgaard; Hagler, Juergen; Nikolic, Lana Tankosa; Polywka, Andrea; Sabra, Jakob Borrits Skov; Vistisen, Peter (Proceedings of CAGA24: The Conference of AG Animation 2024, 2025)
This is the editorial for the CAGA24 proceedings.